PREPARING STUDENTS FOR PROFESSIONAL ACTIVITY AS A PEDAGOGICAL PROBLEM BASED ON AN INNOVATIVE APPROACH (Scientific Conference on Multidisciplinary Studies, 2025)
This article analyzes current challenges in preparing students for professional activities using an innovative approach. It discusses recent reforms in the education system, presidential decrees and resolutions aimed at developing education, as well as scientific recommendations for addressing the tasks outlined in these documents. The article presents pedagogical aspects of preparing future engineers for professional activities, foreign experiences, and the root causes of emerging problems.